Teológushallgatók doktorálása pedagógiából a debreceni egyetemen 1949-ig - Vincze, Tamás (Gerundium, 2015)
THE DOCTORAL STUDIES OF THEOLOGY STUDENTS AT THE UNIVERSITY OF DEBRECEN UNTIL 1949. Based on the minutes of the doctoral culminative exams at the Faculty of Arts of the University of Debrecen before 1949, the essay comes to the conclusion that numerous doctoral students in the Faculty of Arts between 1917–1949 completed their studies as students of the Faculty of heology. It has been proven that it is not only a unique practice in Debrecen, but it is a continuation of an established practice in Kolozsvár. he author decsribes the practice in Kolozsvár and how it was adapted at the University of Debrecen. Based on some memoirs, the author shows that numerous signiicant representatives of Pedagogy started their careers as students of Theology.